mRNA Transcriptomics of Galectins Unveils Heterogeneous Organization in Mouse and Human Brain - John, Sebastian; Mishra, Rashmi (Frontiers in Molecular Neuroscience, 2016)
Background: Galectins, a family of non-classically secreted, β-galactoside binding proteins is involved in several brain disorders; however no systematic knowledge on the normal neuroanatomical distribution and functions of galectins exits. Hence, the major purpose of this study was to understand spatial distribution and predict functions of galectins in brain and also compare the degree of conservation vs. divergence between mouse and human species. The latter objective was required to determine the relevance and appropriateness of studying galectins in mouse brain which may ultimately enable us to extrapolate the findings to human brain physiology and pathologies. Results: In order to fill this crucial gap in our understanding of brain galectins, we analyzed the in situ hybridization (ISH) and microarray data of adult mouse and human brain respectively, from the Allen Brain Atlas, to resolve each galectin-subtype’s spatial distribution across brain distinct cytoarchitecture. Next, transcription factors (TFs) that may regulate galectins were identified using TRANSFAC software and the list obtained was further curated to sort TFs on their confirmed transcript expression in the adult brain. Galectin-TF cluster analysis, gene-ontology annotations and co-expression networks were then extrapolated to predict distinct functional relevance of each galectin in the neuronal processes. Data shows that galectins have highly heterogeneous expression within and across brain sub-structures and are predicted to be the crucial targets of brain enriched TFs. Lgals9 had maximal spatial distribution across mouse brain with inferred predominant roles in neurogenesis while LGALS1 was ubiquitously expressed in human. Limbic region associated with learning, memory and emotions and substantia nigra associated with motor movements showed strikingly high expression of LGALS1 and LGALS8 in human vs. mouse brain. The overall expression profile of galectin-8 was most preserved across both these species, however, galectin-9 showed maximal preservation only in the cerebral cortex. Conclusions: It is for the first time that a comprehensive description of galectins’ mRNA expression profile in brain is presented. Results suggests that spatial transcriptome changes in galectins may contribute to differential brain functions and evolution across species that highlights galectins as novel signatures of brain heterogeneity and functions, which if disturbed, can promote several brain disorders.